ADSORPTION OF GIBBERELLIC ACID (GA3) ONTO ACID ACTIVATED KAOLIN - Sunardi Sunardi; Yateman Yateman Arryanto; Sutarno Sutarno (Universitas Gadjah Mada, 2010)
Preparation, activation and adsorption study of natural kaolin from Tatakan, Tapin, South Kalimantan have been conducted. The activation of kaolin was done using 6 M HCl solutions at 90 °C for 3 h. The characterizations of kaolin were carried out by Fourier Transform Infrared, X-ray diffraction, and surface area analyzer. Adsorption parameters studied included the effect of pH, contact time, and concentration of gibberellic acid (GA3) onto kaolin samples. The amount of gibberellic acid adsorbed was determined using UV spectrophotometer. The adsorption capacity of kaolin was determined by Langmuir adsorption isotherm model. The result showed that activation of kaolin was resulted the larger specific surface area and more homogeneous composition of kaolin without any destruction of kaolin structure. Adsorption of gibberellic acid onto kaolin before and after activation showed that optimal adsorption was obtained at pH » 7 and reached the equilibrium within 4 h. The calculations result by Langmuir adsorption isotherm model showed that the increasing of adsorption capacity of acid activated kaolin is about 35%.